The Conqueror Worm: recent advances with cholinergic anthelmintics and techniques excite research for better therapeutic drugs. Issue 4 (July 2015) - Martin, R.J.; Puttachary, S.; Buxton, S.K.; Verma, S.; Robertson, A.P.
Abstract The following account is based on a review lecture given recently at the British Society of Parasitology. We point out that nematode parasites cause very widespread infections of humans, particularly in economically underdeveloped areas where sanitation and hygiene are not adequate. In the absence of adequate clean water and effective vaccines, control and prophylaxis relies on anthelmintic drugs. Widespread use of anthelmintics to control nematode parasites of animals has given rise to the development of resistance and so there is a concern that similar problems will occur in humans if mass drug administration is continued. Recent research on the cholinergic anthelmintic drugs has renewed enthusiasm for the further development of cholinergic anthelmintics. Here we illustrate the use of three parasite nematode models, Ascaris suum, Oesophagostomum dentatum and Brugia malayi, microfluidic techniques and the Xenopus oocyte expression system for testing and examining the effects of cholinergic anthelmintics. We also show how the combination of derquantel, the selective nematode cholinergic antagonist and abamectin produce increased inhibition of the nicotinic acetylcholine receptors on the nematode body muscle. We are optimistic that new compounds and combinations of compounds can limit the effects of drug resistance, allowing anthelmintics to be continued to be used for effective treatment of human and animal helminth parasites.